Hemimandibulectomy with full angular mandibular plate reconstruction follicular Ameloblastoma patient - Bulan, Susanti; Ardianto, Andri; Yohana, Raden (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2016)
Introduction : Lip pits are unusual congenital anomalies affecting the lip, first described by DeMurquay in 1845. Lip pits can encounter aesthetic problem thus the patient ask for surgical overcome. Case Report : A 4-year-old girl patient came with double lower lip pits that present since birth with bilateral cleft lip and palate. The pits made a mucous accumulation occurs during mealtimes and crying, and felt aesthethic discomfort. The surgery was performed by simple excision combined with split-lip advancement technique under general anaesthesia and the excised pits was then analized for histopatological structures. The patient has no aesthetic defect after surgery. Discussion : Congenital lip pits are developmental anomalies that occur as an isolated defect or either in association with other developmental disturbances. It happens due to notching of lip at an early stage of development with fixation of tissues of the base of the notch or from a failure of complete union of embryonic lateral sulci of the lip. Lip pits can be shallow or deep, and may be associated with accessory salivary glands. The treatment is usually surgical excision with removal of entire fistulous tract. Conclusion : Surgical removal of lip pits is commonly for cosmetic purpose. It must be treated wisely because lips are essential part of someones face.